2006
DOI: 10.1016/s0022-5347(06)00258-8
|View full text |Cite
|
Sign up to set email alerts
|

Botulinum-A Toxin Injections Into the Detrusor Muscle Decrease Nerve Growth Factor Bladder Tissue Levels in Patients With Neurogenic Detrusor Overactivity

Abstract: Purpose:We investigated the effects of BTX-A on visceral afferent nerve transmission by measuring bladder tissue NGF levels in patients with neurogenic detrusor overactivity before and after intravesical treatment with BTX-A. We also compared the bladder tissue NGF content with clinical and urodynamic data. Materials and Methods: A total of 23 patients underwent clinical evaluation and urodynamics with detection of the UDC threshold, maximum pressure and maximum cystometric capacity before, and at the 1 and 3-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 19 publications
1
84
0
6
Order By: Relevance
“…Intravesical BTX-A injection lowers the NGF content in the bladder tissue of patients with neurogenic detrusor overactivity; however, it is unknown whether reduced bladder NGF results from decreased production, reduced uptake or a combination of both. 90 …”
Section: Inhibition Of Nerve Growth Factor Release and Receptor Transmentioning
confidence: 99%
“…Intravesical BTX-A injection lowers the NGF content in the bladder tissue of patients with neurogenic detrusor overactivity; however, it is unknown whether reduced bladder NGF results from decreased production, reduced uptake or a combination of both. 90 …”
Section: Inhibition Of Nerve Growth Factor Release and Receptor Transmentioning
confidence: 99%
“…In vitro and in vivo experimental studies suggest that the long-lasting effect of the BoNT/A injection in the detrusor muscle could be attributed to the lack of axonal sprouting, as observed in detrusor biopsies after toxin injection (Haferkamp et al, 2004). Studies on biopsies from patients with neurogenic overactive bladder who receive an intradetrusor BoNT/A injection (Apostolidis et al, 2006;Giannantoni et al, 2006), however, have shown decreased levels of sensory receptors P2X3, TRPV1 and NGF, thereby suggesting that BoNT/A may act by reducing the afferent nervous transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In both neural and bladder tissue, BoNT/A affected the release of numerous sensory transmitters other than ACh, including adenosine triphosphate (ATP), substance P, calcitonin gene related peptide (CGRP), and glutamate. BoNT/A may also interfere with vesicle trafficking (Apostolidis et al, 2006), expression of sensory receptors (Apostolidis et al, 2005) and nerve growth factor (NGF) in the bladder wall (Giannantoni et al, 2006). It is therefore likely that in addition to a direct effect on detrusor motor innervation, BoNT/A also modulates intrinsic bladder reflexes through a multimodal effect on sensory pathways.…”
Section: Botulinum a Toxin As Second Line Treatment For Refractory Dementioning
confidence: 99%
“…NGF levels can be reduced along with symptom improvement after intradetrusor botulinum toxin treatment (231,385). Animal studies also demonstrated that the production of neurotrophic factors including NGF increases in the bladder after SCI (661) and chronic administration of NGF into the spinal cord or into the bladder wall in rats induces bladder overactivity and increases excitability of bladder afferent neurons (366,698,740).…”
Section: Disease-induced Changes In Micturition Spinal Cord Injury Anmentioning
confidence: 99%